2017
DOI: 10.1016/j.exger.2017.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Associations of 24-hour sleep duration and CT-derived measurements of muscle and bone: The AGES-Reykjavik Study

Abstract: Background Although the importance of sleep on preservation of several physiological functions is well known, the relationship with the two interconnected tissues — muscle and bone is less understood. Objectives This study aimed to examine the association of 24-hour sleep duration with mid-thigh muscle composition and proximal femur volumetric bone mineral density (vBMD). Methods 2,438 men and 3326 women aged 66 to 96 years, residents in the Reykjavik area, were included in this cross-sectional study. Prox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…The current literature on the association between selfreported sleep duration and BMD in men is mixed. Some studies found that both long [16,[25][26][27]30] and short [12,15,16,20,23] sleep duration are associated with low BMD; however, some studies did not show any association [11,13,29]. The lack of a significant association between BMD and sleep duration in older men in the current study is similar to findings from three prior studies in middle-aged and older men.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The current literature on the association between selfreported sleep duration and BMD in men is mixed. Some studies found that both long [16,[25][26][27]30] and short [12,15,16,20,23] sleep duration are associated with low BMD; however, some studies did not show any association [11,13,29]. The lack of a significant association between BMD and sleep duration in older men in the current study is similar to findings from three prior studies in middle-aged and older men.…”
Section: Discussionsupporting
confidence: 84%
“…The lack of a significant association between BMD and sleep duration in older men in the current study is similar to findings from three prior studies in middle-aged and older men. An analysis of a similar-aged cohort of 2438 older men from the AGES-Reykjavik Study [11] identified no association between self-reported sleep duration (including naps) and volumetric BMD. No association was identified between self-reported sleep duration and BMD by calcaneal ultrasound in 3950 middle-aged Chinese men, where 8-9 h/ night was used as the reference group [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both long 2 10 or short 4 , 5 , 7 , 8 , 11 13 self-reported sleep duration have been associated with low bone mineral density (BMD)/osteoporosis or fracture in the literature. Some, studies have not reported an association between sleep duration and BMD 14 , 15 . However, in these studies, the diagnostic methods used for osteoporosis varied considerably, including self-reported osteoporosis fracture, BMD by ultrasonic bone densitometry, peripheral quantitative computed tomography, or dual-energy X-ray absorptiometry (DXA) 2 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Both long [13, 6875] and short [70, 71, 7480] self-reported sleep duration have been associated with low BMD/osteoporosis or fracture in previous, mostly cross-sectional, studies (Table 1). In addition, one study found that long (≥8 h) compared to short (<6 h) sleep duration was associated with an increased risk of osteoporosis [81] and two studies reported no association between sleep duration and BMD [82, 83]. A recent meta-analysis [84] determined that long sleep duration (defined as ≥8 h/day) was associated with a 22% higher risk of osteoporosis in middle-aged and elderly women (OR 1.22, 95% CI 1.06–1.38), while no association was identified for women with short sleep duration (defined as ≤7 h/day).…”
Section: 0 Associations Among Shift Work the Associated Sleep/circmentioning
confidence: 99%